Education in Socio-emotional and Citizen Competencies and a Culture of Peace through Art (Docentes 2.0 Journal, 2025)
In the educational field, problems related to school coexistence, emotional imbalance of students, and poor academic performance represent complex challenges that require comprehensive solutions. This research explored how art, integrated into the educational context, can effectively strengthen emotional, social, and civic skills at the Yatí Educational Institution. Under the methodology of action research method, positivist paradigm, qualitative approach, with a descriptive participatory action research design. The sample included 156 key participants selected through convenience sampling: students, teachers, directors, and parents. Through participant observation, documentary review, and open interviews, preliminary results show that art promotes the development of socio-emotional skills, fosters values ??of peaceful coexistence, and strengthens ties within the educational community. It is concluded that integrating art into educational processes generates empathetic and socially committed citizens.
Keywords: Art; socio-emotional competences; civic competences; school coexistence; culture of peace